Mele Lāhui: The Importance of Pono in Hawaiian Poetry - Basham, Leilani (Te Kaharoa, 2008)
Mele, which are poetry, music, chants, and songs, have been a foundational part of the histories and lives of the Kānaka Maoli of Hawai’i. This article examines some of the concepts contained within Mele, and reveals their intricate cultural contribution to the world-view of the indigenous people of Hawai’i.